Simple dissymmetrical and asymmetrical Tröger's bases: Photophysical and structural characterization - Trupp, Leandro Julián (2020)
Despite their continuously growing preparation and applications in the last decades, the photophysical properties of Tröger’s bases (TBs) with small substituents have not been analyzed. We synthetized three dissymmetrical TBs with amino, isocyano and formamido groups and a new asymmetrical TB with one amino and one isocyano group and studied their absorption and emission properties and solvatochromic effects. An intramolecular charge transfer (ICT) state was found for the isocyano containing derivatives, associated to the isocyano acceptor group and the nitrogen donor atom in the central diazocinic core. NMR and IR spectroscopy were also analyzed, demonstrating the communication between both ends of the TBs.